The role of Notch ligand Jagged1 in osteosarcoma proliferation, metastasis, and recurrence - Jianping Zhang; Na Li; Siyu Lu; Yanling Chen; Lequn Shan; Xingcheng Zhao; Yongqing Xu (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Osteosarcoma is the most common primary bone cancer occurring in young adults and the 5-year survival rate of patients with metastatic osteosarcoma is less than 30% due to high metastatic recurrence and drug resistance. Notch is a highly conserved cell to cell signaling pathway in evolution, and Jagged1 is an important ligand of Notch. Although some studies have found that Notch receptors and ligands including Jagged1 were highly expressed in osteosarcoma tissues and osteosarcoma cells, the role of Jagged1 in osteosarcoma progression and metastasis are still not clear. Methods Tumor tissues were collected from 68 patients and immunohistochemical staining was employed to group these patients by expression of Jagged1. Real-time quantitative PCR and Western blotting were used to detect the expression of Jagged1. We used siRNA to knockdown the expression of Jagged1 in F5M2 cells. Colony formation assay and MTT were employed to detect and analyze the proliferation of F5M2 cells with or without knockdown of Jagged1. Transwell assay were used to detect the migration and invasion of F5M2 cells. Results In this study, we found that the high expression of Jagged1 is closely related to the metastasis and recurrence of osteosarcoma in 68 clinical specimens. The expression of Jagged1 in F5M2 cells with high metastasis was significantly higher than that in F4 cells with low metastasis. Knockdown of Jagged1 led to lower ability of proliferation, migration, and invasion in F5M2 cells. Conclusion The high expression of Jagged1 is closely related to the metastasis and recurrence of osteosarcoma. Knockdown of Jagged1 significantly reduced the proliferation, migration, and invasion of osteosarcoma cells. Our results suggested that knockdown of Jagged1 may be a potentially effective treatment for metastatic osteosarcoma.